NILAI HBA1C DAN KEPARAHAN PENYAKIT JANTUNG KORONER - Aneka Pristi Ria Rimbayani; Noerma Shovie Rizqiea; Dewi Suryandari (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Coronary Heart Disease (CHD) remains the leading cause of death worldwide. Among the numerous risk factors influencing the severity of coronary angiography outcomes, diabetes mellitus stands out, with its impact measured through the HbA1c parameter. Objective: This study aimed to determine the relationship between HbA1c levels and the severity of CHD in the Cardiac Catheterization Room. Method: The research adopted a quantitative and observational approach with a cross-sectional design. The population consisted of CHD patients who underwent diagnostic and interventional coronary angiography. The sampling technique utilized purposive sampling of 59 patients. The severity of CHD was measured using the Sullivan Vessel Score. Statistical data was analyzed using the Spearman test. Result: The results revealed that most respondents were male accounting for 47 (79.7%) individuals, the most HbA1c values were in the pre-diabetes category for 23 (39%) respondents. The most prevalent severity classification was CAD1V for 27 (45.8%) respondents. Conclusion: Bivariate analysis indicated no significant relationship between HbA1c values and CHD severity (p-value 0.415). The correlation coefficient value of 0.108 indicated a promising positive relationship direction.